On the spectral data of perturbed Stark operators in the half-line with mixed boundary conditions - Toloza, Julio Hugo (2023)
We discuss some asymptotic formulas for the spectral data of perturbed Stark operators associated with the differential expression − d 2 dx2 + x + q(x), x ∈ [0, ∞), q ∈ L 1 (0, ∞), and boundary condition φ ′ (0) − bφ(0) = 0, b ∈ R.